Animation-Based Learning Motivation Analysis on Human Digestive System Material to Evaluate Students’ Motivation - Jaharuddin Tanjung; Hasmi Syahputra Harahap (Lectura : Jurnal Pendidikan, 2023)
This study aims to evaluate students’ indication-based learning motivation as well as the level of animation-based learning motivation in the class XI Ilmu Pengetahuan Alam (IPA) at Sekolah Menengah Atas (SMA) Negeri 2 Rantau Utara on human digestive system material. Descriptive statistical analysis is used in the research method’s quantitative component. Out of the 141 students in the XI Science class, 105 participants were randomly chosen from three classrooms using a purposive sampling technique. Instrument testing was done to ascertain the reliability and accuracy of the angles, questioner. The study’s methodology used the Student Learning Motivation Questionnaire. Data analysis techniques using quantitative descriptive analysis assisted by SPSS for Windows program. The findings revealed that students in class XI IPA 1 had extremely high levels of learning motivation (82.09), class XI IPA 2 had good levels 72.31, and XI IPA 3 had low levels 64.77 (good). Student motivation is measured by indicators such as persistence in learning, which has an average value of 77.65(good), tenacity in overcoming challenges, which has a value of 72.51(good), interest in learning, which has a value of 82.57(very good), achievement in learning, which has a value of 81.10(very good), and independent indicator in learning, which has a value of 74.21(good). Teachers should be able to use learning innovations like animated media or other interactive media to continue motivating students to learn as a result of this study’s follow-up findings. This will ensure that students are always interested in what they are learning.